(untitled) (Global Journal of Medical Research, 2015)
Objective: To assess several socioeconomic variables and their association with benign prostatic hyperplasia (BPH). Patients and methods: A hospital based prospective study comprised 209 patients (aged 36 - 90 years, mean age for 9.5 years) surgically treated for BPH within one year of its diagnosis (cases). All cases were from rural area. We classified men with clinical BPH at the follow - up if they reported (1) frequent or difficulty urinating and were told by a health professional that they had a n enlarged or swollen prostate or (2) if they reported having surgery for BPH. Each participant completed a standardized questionnaire, including socioeconomic status, use of cigarettes, alcohol and coffee consumption. The questionnaire also elicited detailed information on the medical history of prostatic and (over the past month) lowers urinary tract symptoms, applying all questions from the American Urology Association instrument.